Causality of the Artificial Intelligence Paradigm on Constructivist Perspective for Student Academic Ethics - Asmarita, Desi; Muyassaroh, Iffah Khoiriyatul; Saptaputra, Idil (Proceeding International Conference on Religion, Science and Education, 2024)
Technological innovation is undeniable as the presence of artificial intelligence have shown a deep and equitable impact in various aspects of life. This transformation covers fundamental sectors, including the higher education sector. This research aims to investigate the causality inherent in the paradigm artificial intelligence towards the context of student academic ethics. This research is a qualitative approach with a type of literature study. Data analysis was carried out using techniques of content analysis. The research results show that the paradigm of artificial intelligence is related to moral ethics in carrying out the mission and duties of the tri dharma of higher education, as well as interactions in the learning process. The constructivist perspective looks at paradigms artificial intelligence as a theoretical framework that underlies collaborative learning methods, the active role of students, dynamic interactions between individuals and their learning context, as well as synergistic system interactions artificial intelligence with human intelligence. The context of student academic ethics in the constructivist approach teaches that students not only accept ethical norms as a teaching, but furthermore, they are active in formulating and internalizing moral principles in the academic context, thereby producing students who have critical thingking, socially interactive, and collaborative skills in utilizing artificial intelligence.